Negoziazioni, dilemmi, opportunità fra antropologia e promozione della salute - Portis, Lucia; D’Ambrosio, Rosanna (Antropologia Pubblica, 2019)
Changing people’s behaviour regarding health is an important challenge, particularly when the interventions are assembled on subjects whose cultural repertoires and/or partner-economic situations are different from those of the operators. Any project of health promotion should begin from the systematic analysis of the health determinants and the life-style of the select target. Many anthropologists have criticized such projects because they give too great emphasis to the cognitive processes and scarce attention to the roots of the human behaviour in cultural contexts. On this basis our article will try to bring into focus what advantages and problems are implicated within the presence of an anthropologist in the department of prevention of a sanitary firm. For this reason, two processes of strategies construction regarding health promotion have been introduced in the community concerning the problems of alcohol abuse and the healthy diet. Both have implicated an initial analysis of the context and the synergy with “others” subjects characterized as stakeholders. They have shown how the presence of the anthropological knowledge is able to deconstruct customs and consolidated practices of healthcare work-ers. This article will show opportunities and dilemmas about anthropology presence and the outlook about health promotion.